Influence of Group Therapy in Psychodrama on the Attachment Style of Children at-Risk: Educational, Emotional, Social, and Behavioral Aspects - Vaxberg, Zivit (Kultura-Społeczeństwo-Edukacja, 2014)
Children at-risk are defined as children who may be found in physical, mental, or emotional situations of risk. Attachment theory assumes a connection between the origin family’s experiences and the attachment patterns in the relations with another person, and many research studies have found that the attachment between the parent and the child has a main role in the child’s normal development. The psychodrama group is one method of intervention that seeks to treat psychological and social problems through drama and provides the child with holding, security, and protection. The children act figures related to problems that trouble them and thus free themselves from distresses and drives and learn to see and understand the self and other people and to create beneficial patterns of behavior and attachment. Treatment with psychodrama has been found to be very effective in work with children who experience distress, both with themselves and with society.